Plus Bouhan: A new community-based approach to crime prevention in Japan - Hino, Kimihiro (International journal of law, crime and justice, 2018)
The number of crime prevention volunteer organizations in Japan has continued to increase and at the end of 2014, there were some 48,000 such organizations with a total of approximately 2.8 million members. However, other statistics show that the majority of volunteers are men in their late seventies In response to this situation, the author advocates the "Plus Bouhan" (Plus Crime Prevention) approach, which adds aspects of crime prevention to daily activities in communities. The aim of this study was to investigate whether two activities carried out by "Plus Bouhan" could diversify the range of crime prevention volunteers and what influence they could have on volunteers' activity and attitude. The first practice added a crime prevention aspect to a daily gardening activity and the second added a crime prevention aspect to walking and jogging. The volunteers completed questionnaires and the results showed that residents who had previously been indifferent to crime prevention activities took part in these activities. In particular, many office workers in their thirties and forties took part in the second activity. These results show the utility of "Plus Bouhan" in diversifying the range of crime prevention volunteers and changing their activity and attitude.